Indomethacin treatment in small versus large premature infants with ductus arteriosus. Comparison of plasma indomethacin concentration and clinical response. Issue 1 (July 1983) - Yeh, T F; Luken, J; Raval, D; Thalji, A; Carr, I; Pildes, R S
Abstract : An analysis of clinical response and plasma indomethacin concentration was performed on 10 small (less than or equal to 1000 g) and 12 large (greater than 1000 g) premature infants who had symptomatic ductus arteriosus and required intravenous indomethacin therapy (0.3 mg/kg per day). The postnatal age, daily fluid intake, and cardiopulmonary status of the two groups at time of study were comparable, The small premature infants had a significantly lower peak plasma indomethacin concentration and lower concentration in the first four hours after infusion, and lower plasma concentration X time integral than that of the larger premature infants. There was a significant difference between the groups in proportion of response (2/10 vs 9/12) after one dose of indomethacin; this difference was not seen after two to three doses. The results of the study suggest that small premature infants do respond to indomethacin treatment, but compared to the larger infants may require repeated doses.